Assessment of Usability and Task Load Demand Using a Robot-Assisted Transfer Device Compared With a Hoyer Advance for Dependent Wheelchair Transfers. (August 2019) - Greenhalgh, Mark; Landis, James Matthew; Brown, Joshua; Kulich, Hailee; Bass, Sarah; Alqahtani, Saleh; Deepak, Nikitha; Cryzter, Theresa Marie; Grindle, Garrett G.; Koontz, Alicia M.; Cooper, Rory A.
Abstract : Objective: Manual lifting can be burdensome for people who care for power wheelchair users. Although technologies used for dependent transfers are helpful, they have shortcomings of their own. This study compares the usability and task load demand of a novel robot-assisted transfer device to a clinical standard when performing dependent transfers. Design: A cross-sectional study was conducted to assess caregivers ( N = 21) transferring a 56-kg mannequin with the Strong Arm and Hoyer Advance at three transfer locations. Feedback was gathered through qualitative surveys. Results: Usability was significant in multiple areas important for transfers. Caregiver fatigue and discomfort intensity were reduced, and the Strong Arm was preferred at the three transfer locations. Device ease and efficiency favored Strong Arm at two stations as was discomfort frequency. In addition, physical demand, frustration, and effort were significantly lower using Strong Arm compared with the Hoyer Advance. Conclusions: Compared with the Hoyer, participants favored Strong Arm for transfer usability and task load demand. However, further Strong Arm developments are needed.